Judicial approaches to determination of earning capacity as matrimonial property; Special reference to UK, USA, Australia and Malaysia Law - Norliah, Ibrahim; Zuhairah Ariff, Abd Ghadas; Hassan, Sackor (2018)
One of the important aspects in managing marriages is property arrangement. The definition of property includes both tangibles and intangibles property. The tangible property is defined by the economists based on goods, physical commodities or product whereas any bodiless or immaterial property such as services are regarded as intangible property. Differentiating between the definitions of both tangibles and intangibles is quite significant, as it records fundamental role in which dividing assets accurately is achieved. In many instances of marriage breakdown, one of the most valuable economic asset is the earning capacity of one or both of them. The question of intangible interest such as human capital and future interests as matrimonial property had been vigorously debated but the policies are still unascertained. This paper discusses the legal approaches of courts in few jurisdictions in dealing with claims on earning capacity as matrimonial property. Research methodology applied in this paper are the statutory and doctrinal analysis.